SUBSTITUTION OF INORGANIC FERTILIZER WITH LIQUID ORGANIC FERTILIZER ON THE GROWTH OF RICE PLANTS SRI METHOD - Rozen, Nalwida; Kasim, Musliar; Dwipa, Indra; Syarif, Auzar; Sutoyo, Sutoyo (Agros Journal of Agriculture Science, 2024)
Increasing rice production has been carried out in various ways. One method that has been implemented is the SRI method which can increase yields up to two times or more, but this method has not been adopted optimally by farmers because of the difficulty in cultivating practices in the field. Apart from that, farmers still use inorganic fertilizers without balancing them with organic fertilizers. One alternative that can be applied is to use organic materials that are available in the rice field environment, namely using liquid organic fertilizer (LOF) from banana stems and coconut fiber which are very easy for farmers to obtain in the field. Apart from the difficulty of getting fertilizer, due to high prices, fertile land has changed its function so that the area for rice cultivation is starting to decrease, but the land that is still widely available is marginal (suboptimal) land with low soil nutrient content and low pH. The aim of this research is to obtain the interaction between the type of LOF and the recommended dose of inorganic fertilizer as a substitute. The research location was carried out in Pasar Ambacang Village, Kuranji District, Padang City from May to November 2023. The research was carried out using a 2-factor factorial design in a Completely Randomized Design (RAL), where the first factor was the type of LOF (banana stem and coconut fiber) and the second factor is the dose of inorganic fertilizer TSP and KCl (0, 25, 50, 75, 100) % recommendation. The results obtained are that providing LOF types with inorganic fertilizers with different recommendations showed an interaction with the leaf area index. The number of stomata is influenced by the type of LOF and inorganic fertilizer, where LOF coconut fiber with 100% inorganic fertilizer gives the best results. Key words: banana stems, yield, fertilizer, coconut fiber, substitution